Undergraduate Kinesiology Students’ Experiences in Online Motor Development Course - Sato, Takahiro; Haegele, Justin A. (Online Learning, 2018)
The purpose of this study was to investigate undergraduate kinesiology students’ experiences in an online life span motor development course. This study was based on theory of transactional distance (Moore, 1997). Seven undergraduate kinesiology majors (5 females, 2 males), who were enrolled in an online course at a Midwestern public university in the US, participated in this study. Data collection included face-to-face open ended interviews, bulletin board discussion logs, and online assessment projects. A constant comparative method was used to interpret the data, and allowed themes to emerge from the data as well as from the theoretical framework. Three interrelated themes emerged from the undergraduate students’ narratives; rigors and flexibility in online course learning, peer feedback experiences, and video assessment analysis. The results of this study demonstrate that undergraduate students can have independent learning styles and kinesthetic characteristics and concepts when enrolled in online life span motor development coursework. Online kinesiology courses should be centered on a set of student tasks (lectures, projects, and assignments) that constitute the learning experiences that engage students, either independently and collaboratively, in order for them to master the objectives of the course (Carr-Chellman & Duchastel, 2001).